Beamforming Algorithms for Adaptive Array Antenna - Nurul Hazlina, Noordin; Zulkeflee, Kalidin (2014)
The radiation pattern of an adaptive array antenna can be optimised by manipulating the amplitude and phase excitation of the array elements. In this paper,different adaptive beamforming algorithms including minimum Mean-Square Error (MSE), power minimisation and maximum Signal to Interference-plus-Noise Ratio (SINR), are compared and discussed. The algorithms are applied to a 3-faceted adaptive array antenna. Simulation results show that the resulting radiation pattern with minimum MSE has higher directivity and lower sidelobe level compared to the other optimisation criteria, which allows the array to avoid more interference signals in a wireless communication system.